ANALISIS POTENSI PERMINTAAN (DEMAND) ANGKUTAN UMUM PADA KORIDOR JALAN RAYA SESETAN DENPASAR - Dewa Ayu Nyoman Sriastuti (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT Denpasar city is the center of government, trade, education, tourism and various services are indicators of changes in land use, density, movement, and high population, impact on economic improvement, social culture and transportation activities, especially traffic activity. Incriesed activities are followed by an increase in private vehicle usage, which causes transportation problems to become more complex. Therefore, transportation system planning especially in terms of transportation is an urgent thing to do. One of the important transportation systems planning to help solve the transportation problem is the planning of public transportation arrangement. Public transport routes in the Denpasar city have not spread evenly to serve the potential demand for public transportation, such as in the area of South Denpasar for example, there is no public transport routes that serve the community to conduct student activities, public transportation, so that necessary to study the potential demand of public transport, especially on Jalan Raya Sesetan corridor in South Denpasar. The service of reliable public transport is solution to create an effective, efficient and economical route in the utilization of road space and fuel consumption. The objective of providing public transportation which effective, efficient and economical will be achieved if the characteristics of users around the planned service corridor mainly concern the potential of public transport demand is known. Characteristics along the service corridor include the number of family members, the number of workers, the number of students, the number of potential trips, the number of vehicles owned, the monthly family income, the interest in the use of public transport. The result shown the average number of population in the service corridor is 21431 in which all villages have an average N value greater than the value of R (R = 20), thus fulfilling in public transport service, while the number of passengers is 17543 movements. Keyword: micro-hydro, soil bearing capacity, foundation design